Mode of action of the COR15a gene on the freezing tolerance of Arabidopsis thaliana - Steponkus, Peter L. (The National Academy of Sciences, 1998)
Constitutive expression of the cold-regulated COR15a gene of Arabidopsis thaliana results in a significant increase in the survival of isolated protoplasts frozen over the range of −4.5 to −7°C. The increased freezing tolerance is the result of a decreased incidence of freeze-induced lamellar-to-hexagonal II phase transitions that occur in regions where the plasma membrane is brought into close apposition with the chloroplast envelope as a result of freeze-induced dehydration. Moreover, the mature polypeptide encoded by this gene, COR15am, increases the lamellar-to-hexagonal II phase transition temperature of dioleoylphosphatidylethanolamine and promotes formation of the lamellar phase in a lipid mixture composed of the major lipid species that comprise the chloroplast envelope. We propose that COR15am, which is located in the chloroplast stroma, defers freeze-induced formation of the hexagonal II phase to lower temperatures (lower hydrations) by altering the intrinsic curvature of the inner membrane of the chloroplast envelope.